2010
DOI: 10.3803/jkes.2010.25.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Pituitary Hyperplasia Induced by Hashimoto's Thyroiditis Related Hypothyroidism: A Case Report

Abstract: Pituitary hyperplasia associated with untreated primary hypothyroidism in children is a rare condition. There are only a few reports on this condition in children, and especially when pituitary hyperplasia is accompanied with Hashimoto thyroiditis and growth arrest. Here, we describe an unusual association of pituitary hyperplasia with hypothyroidism and growth retardation, and this was all caused by Hashimoto thyroiditis. Hormonal testing showed a low thyroxine level and a high thyroid stimulating hormone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…A 15-year-old boy with short stature and increased weight gain, who was found to have primary hypothyroidism (thyroid-stimulating hormone [TSH] >100 mIU/mL, free T4 = 0.64 pmol/L), with elevated anti-TPO antibodies (>3000 IU/mL) was described. 3 His neuroimaging was suggestive of a pituitary macroadenoma, without any evidence of focal neurological deficit and normal levels of pituitary hormones except for mild elevation of prolactin (21.02 µg/L) as in our patients. He was started on oral levothyroxine (100 mcg/day), following which thyroid function tests and prolactin levels normalised, and repeat neuroimaging showed reduction of pituitary size to normal.…”
Section: Discussionsupporting
confidence: 63%
“…A 15-year-old boy with short stature and increased weight gain, who was found to have primary hypothyroidism (thyroid-stimulating hormone [TSH] >100 mIU/mL, free T4 = 0.64 pmol/L), with elevated anti-TPO antibodies (>3000 IU/mL) was described. 3 His neuroimaging was suggestive of a pituitary macroadenoma, without any evidence of focal neurological deficit and normal levels of pituitary hormones except for mild elevation of prolactin (21.02 µg/L) as in our patients. He was started on oral levothyroxine (100 mcg/day), following which thyroid function tests and prolactin levels normalised, and repeat neuroimaging showed reduction of pituitary size to normal.…”
Section: Discussionsupporting
confidence: 63%
“…From a review of previously published case reports in Korean children, we found six cases that affected 4 boys and 2 girls [10][11][12][13][14] . The mean age was 8 years and 6 months, ranging between 2 and 15 years, and all patients were initially referred to a endocrinologist for growth arrest.…”
Section: Discussionmentioning
confidence: 99%